3/7 +-10/21 -4/3
4/9:2 ; 3/5:2 ;10/21:5 ;6/7:3 ;5/7:3 ;2/3:4
Tính:
a, 5/-14. 7/-19
b, -15/4 .( 16/-25 )
c, 3/-10 .( -15/-2 )
d, -5/7 . ( 21/-10 )
e, 10/-3. (6/-5)
f, 21/-9 . ( -6/14 )
g, -10/9 . ( 36/20 )
a, 5/-14. 7/-19=8/38
b, -15/4 .( 16/-25 )=12/5
c, 3/-10 .( -15/-2 )=
d, -5/7 . ( 21/-10 )=-9/4
e, 10/-3. (6/-5)==4
f, 21/-9 . ( -6/14 )=1
g, -10/9 . ( 36/20 )=-2
a)(-0,25).4/17.(-3 5/21).(-7/12)
b) (-2/5).4/15+(-3/10).4/15
c)21-3 3/4:(3/8-1/6)
d) (-3/4+2/5):3/7+(3/5+-1/4):3/7
GIÚP MÌNH VỚI Ạ. MÌNH CẦN GẤP VÀO SÁNG NAY. CẢM ƯN NỌI NGƯỜI NHÌU!
a)(-0,25).4/17.(-3 5/21).(-7/12)
= -1/17 . (-68/21) . ( -7/21)
= -4/63
b) (-2/5).4/15+(-3/10).4/15
= 4/15. [-2/5 + (-3/10)]
= 4/15 . (-7/10)
= -14/75
c)21-3 3/4:(3/8-1/6)
= 21 - 15/4 : 5/24
= 21 - 18
= 3
d) (-3/4+2/5):3/7+(3/5+-1/4):3/7
= [(-3/4 + 2/5) + (3/5 + -1/4)] : 3/7
= [-7/20 + (-17/20)] : 3/7
= -6/5 : 3/7
= -14/5
Tính
A, 3 × 5/4 - 3^2/4
B, -3/2 × ( 7/3 - 5/3 × 4 )
C, -21/10 + 21/10 × 3/4 - 3/4
D, -2/3 + 2 × ( -2/3 ) × 3 - 3
A . \(3\cdot\dfrac{5}{4}-\dfrac{3^2}{4}=\dfrac{15}{4}-\dfrac{9}{4}=\dfrac{6}{4}=\dfrac{3}{2}\)
B, \(\dfrac{-3}{2}\cdot\left(\dfrac{7}{3}-\dfrac{5}{3}\cdot4\right)=\dfrac{-3}{2}\cdot\left(\dfrac{7}{3}-\dfrac{20}{3}\right)=\dfrac{-3}{2}\cdot\dfrac{-13}{2}=\dfrac{39}{4}\)
C , \(\dfrac{-21}{10}+\dfrac{21}{10}\cdot\dfrac{3}{4}-\dfrac{3}{4}=\dfrac{-84}{40}+\dfrac{63}{40}-\dfrac{30}{40}=\dfrac{-84+63-30}{40}=\dfrac{-51}{40}\)
D , \(\dfrac{-2}{3}+2\cdot\left(\dfrac{-2}{3}\right)\cdot3-3=\dfrac{-2}{3}\left(1+2\cdot3\right)-3=\dfrac{-2}{3}\cdot7-3=\dfrac{-14}{3}-\dfrac{9}{3}=-\dfrac{23}{3}\)
a ) 10/3 - 8/3
11/4 - 5/4
32/17 + 21/17
b ) 5/6 + 7/8
3/7 - 5/14
7/4 - 3/5
Help
a: 10/3-8/3=2/3
11/4-5/4=6/4=3/2
32/17+21/17=53/17
b: 5/6+7/8=20/24+21/24=41/24
3/7-5/14=6/14-5/14=1/14
7/4-3/5=35/20-12/20=23/20
a: 10/3-8/3=2/3
11/4-5/4=6/4=3/2
32/17+21/17=53/17
b: 5/6+7/8=20/24+21/24=41/24
3/7-5/14=6/14-5/14=1/14
7/4-3/5=35/20-12/20=23/20
a: 10/3-8/3=2/3
11/4-5/4=6/4=3/2
32/17+21/17=53/17
b: 5/6+7/8=20/24+21/24=41/24
3/7-5/14=6/14-5/14=1/14
7/4-3/5=35/20-12/20=23/20
Tính: M= (13 1/4-2 5/21-10 5/6)x230 1/25+46 3/4/(1 3/7+10/3):(12 1/3-14 2/7)
help me
-4/7-x=3/5-2x
3/7.x-2/3.x=10/21
\(-\dfrac{4}{7}-x=\dfrac{3}{5}-2x\\ \Rightarrow-x+2x=\dfrac{3}{5}+\dfrac{4}{7}\\ \Rightarrow x=\dfrac{21}{35}+\dfrac{20}{35}\\ \Rightarrow x=\dfrac{41}{35}\)
Vậy `x=41/35`
__
\(\dfrac{3}{7}x-\dfrac{2}{3}x=\dfrac{10}{21}\\ \Rightarrow\left(\dfrac{3}{7}-\dfrac{2}{3}\right)x=\dfrac{10}{21}\\ \Rightarrow\left(\dfrac{9}{21}-\dfrac{14}{21}\right)x=\dfrac{10}{21}\\ \Rightarrow\dfrac{-5}{21}x=\dfrac{10}{21}\\ \Rightarrow x=\dfrac{10}{21}:\left(-\dfrac{5}{21}\right)\\ \Rightarrow x=-2\)
Vậy `x=-2`
a)
-4/7 - x = 3/5 - 2x
2x - x = 3/5 + 4/7
x = 41/35
Vậy x = 41/35
b)
3/7.x - 2/3.x = 10/21
x(3/7 - 2/3) = 10/21
x.(-5/21) = 10/21
x = 10/21 : (-5/21) = -2
Vậy x = -2
14. √(7-4√3)
15. √(8+2√15)
16. √(10-2√21)
17. √(11+2√18)
18. √(7+2√10)
19. √(7+4√3)
20. √(12-2√35)
14) \(\sqrt{7-4\sqrt{3}}=2-\sqrt{3}\)
15) \(\sqrt{8+2\sqrt{15}}=\sqrt{5}+\sqrt{3}\)
16) \(\sqrt{10-2\sqrt{21}}=\sqrt{7}-\sqrt{3}\)
17) \(\sqrt{11+2\sqrt{18}}=3+\sqrt{2}\)
18) \(\sqrt{7+2\sqrt{10}}=\sqrt{5}+\sqrt{2}\)
19) \(\sqrt{7+4\sqrt{3}}=2+\sqrt{3}\)
20) \(\sqrt{12-2\sqrt{35}}=\sqrt{7}-\sqrt{5}\)
\(\sqrt{7-4\sqrt{3}}=\sqrt{2^2-2.2.\sqrt{3}+\left(\sqrt{3}\right)^2}=\sqrt{\left(2-\sqrt{3}\right)^2}=\left|2-\sqrt{3}\right|=2-\sqrt{3}\)
√7−4√3=√22−2.2.√3+(√3)2=√(2−√3)2=∣∣2−√3∣∣=2−√3
( 1+ 1/2 ) . ( 1+ 1/3 ) . ( 1+ 1/4 )
1/5 : 1/10 - 1/3 ( 6/5 - 9/4 )
-7/8 : 21/16 - 3/5 . ( 1/5 - 7/10 )
a: \(=\dfrac{3}{2}\cdot\dfrac{4}{3}\cdot\dfrac{5}{4}=\dfrac{5}{2}\)
b: \(=\dfrac{1}{5}\cdot10-\dfrac{1}{3}\cdot\dfrac{24-45}{20}=2-\dfrac{-7}{20}=2+\dfrac{7}{20}=\dfrac{47}{20}\)
c: \(=\dfrac{-7}{8}\cdot\dfrac{16}{21}-\dfrac{3}{5}\cdot\dfrac{-1}{2}\)
\(=\dfrac{-2}{3}+\dfrac{3}{10}=\dfrac{-20+9}{30}=\dfrac{-11}{30}\)
( 1+ 1/2 ) . ( 1+ 1/3 ) . ( 1+ 1/4 )=5/2
1/5 : 1/10 - 1/3 ( 6/5 - 9/4 )=47/20
-7/8 : 21/16 - 3/5 . ( 1/5 - 7/10 ) =-11/30
( 1+ 1/2 ) . ( 1+ 1/3 ) . ( 1+ 1/4 )=3/2 . 4/3 . 5/4 =5/2
1/5 : 1/10 - 1/3 ( 6/5 - 9/4 )=2 - 1/3 . -21/20=2 + 7/20=47/20
-7/8 : 21/16 - 3/5 . ( 1/5 - 7/10 ) =-2/3 + 3/10=-11/30